Electrophysiological findings during atrial fibrillation reablation: Extending from pulmonary vein reconnection to sequential bipolar voltage map information. (20th February 2020) - Huo, Yan; Kronborg, Mads Brix; Richter, Utz; Guo, Jianping; Ulbrich, Stefan; Zedda, Angela M.; Kirstein, Bettina; Mayer, Julia; Pu, Liying; Piorkowski, Judith; Wagner, Michael; Gaspar, Thomas; et al.
Abstract: Background: Left atrial substrate modification targeting low voltage zones (LVZ) is an ablation strategy that—in addition to pulmonary vein (PV) isolation—tries to eliminate arrhythmogenic mechanisms harbored in such tissue. Electrophysiological findings at reablation include (a) PV reconnection, (b) reconnection over previous substrate ablation, and (c) de‐novo LVZ. Objective: To study, prevalence and contribution of these arrhythmogenic electrophysiological entities in patients with atrial fibrillation (AF) recurrences. Methods: Consecutive patients with highly symptomatic AF undergoing index and reablation were included (n = 113). In all patients' PV reconnection, reconnection over previous substrate ablation and spontaneous de‐novo LVZ were quantitatively assessed and integrated into an individual reablation strategy. Follow‐up was based on continuous device monitoring. Results: At re‐do procedure, 45 out of 113 (39.8%) patients showed PV reconnection as the only electrophysiological abnormality. Reconduction over previous lines was the only electrophysiological abnormality in 8 out of 113 (7.1%) patients. Spontaneous de‐novo LVZ was the only electrophysiological abnormality in 12 out of 113 (10.6%) patients. Combined findings of PV reconnection, line reconduction, and/or spontaneous de‐novo LVZ were seen in 40 out of 113 (35.4%) patients. No detectable electrophysiological abnormality was observed in 8 out of 113 (7.1%) patients. In univariate analysis, none of the tested electrophysiological characteristics independently predicted the outcome after re‐do. Conclusions: In patients undergoing reablation, we could show that reconduction over previous substrate ablation as well as the development of new low voltage areas are frequent findings besides classical PV reconnection—without a clear leading cause for recurrences. These findings impact reablation strategies as well as the strategic focus during index procedures.